Adapting to intersectoral transfers in the Zhanghe Irrigation System, China: Part II - Impacts of in-system storage on water balance and productivity - Roost Nicolas; Xueliang Cai; Turral, Hugh; David, S.; Yuanlai Cui (2008)
This paper investigates the impacts of farm ponds in a context of declining supplies in a major canal command within the Zhanghe Irrigation System (ZIS), in Central China. As dam supplies have been diverted to higher-valued uses (hydropower, cities and industry), farmers have responded by constructing small storages within their fields. These farm ponds have given them sufficient flexibility in water supply to practice varying forms of alternate wetting and drying irrigation for rice without compromising yields and incomes. Ponds are recharged by a combination of return flows from irrigation and runoff from catchment areas within the irrigated perimeter. Various scenarios of water supply incorporating the main reservoir, in-system reservoirs, farm ponds and irrigation practices were simulated using the OASIS model. OASIS integrates surface and groundwater flows, and contains a crop growth module to aggregate the impacts of different water management regimes. The modelling and sensitivity analysis show that further reductions in main reservoir supplies will have a negative effect on rice production in dry and average years, and that ponds have played a crucial role in adapting agriculture to reduced canal supplies. The flexibility allowed by the ponds has resulted in increased water productivity, except in high rainfall years, but net depletion has not decreased, as local supplies have substituted for water from the main reservoir. The study demonstrates the importance of properly accounting for return flows and the necessity to understand crop production in relation to the actual depletion of water (as evapotranspiration) within an irrigation system.